Perceived Parenting Style and Their Relationship: Self-Identity and Social Competence among Adolescent Students - Razan Jalal Khalaf Alabddi (Program Studi Psikologi Universitas Pendidikan Indonesia, 2023)
This study aimed to study the adolescent student’s perceived parenting style, and their relationship to the concept of self-identity and social competence among adolescent students in Jordan. To achieve these goals, the study followed the descriptive method and pearson correlation analysis, with a questionnaire as a study tool. This was applied to a sample made up of 500 public school students in Jordan for the age group between 14-15 years. The study found that the most prominent techniques for parenting for both parents included dialogue, acceptance, bear the responsibility, and cooperation. The degree of the concept of self-identity and social competence was medium. The results showed the existence of a positive relationship between perceived parenting style and self-identity also social competence.